Characterization of an adaptive immune response in microsatellite-instable colorectal cancer - Boissière-Michot, Florence; Lazennec, Gwendal; Frugier, Hélène; Jarlier, Marta; Roca, Lise; Duffour, Jacqueline; Du Paty, Emilie; Laune, Daniel; Blanchard, France; Le Pessot, Florence; Sabourin, Jean-Christophe; Bibeau, Frédéric (Oncoimmunology, 2014)
Sporadic or hereditary colorectal cancer (CRC) with microsatellite instability (MSI) is frequently characterized by inflammatory lymphocytic infiltration and tends to be associated with a better outcome than microsatellite stable (MSS) CRC, probably reflecting a more effective immune response. We investigated inflammatory mechanisms in 48 MSI CRCs and 62 MSS CRCs by analyzing: (1) the expression of 48 cytokines using Bio-Plex multiplex cytokine assays, and (2) the in situ immune response by immunohistochemical analysis with antibodies against CD3 (T lymphocytes), CD8 (cytotoxic T lymphocytes), CD45RO (memory T lymphocytes), T-bet (Th1 CD4 cells), and FoxP3 (regulatory T cells). MSI CRC exhibited significantly higher expression of CCL5 (RANTES), CXCL8 (IL-8), CXCL9 (MIG), IL-1β, CXCL10 (IP-10), IL-16, CXCL1 (GROα), and IL-1ra, and lower expression of MIF, compared with MSS CRC. Immunohistochemistry combined with image analysis indicated that the density of CD3 + , CD8 + , CD45RO + , and T-bet + T lymphocytes was higher in MSI CRC than in MSS CRC, whereas the number of regulatory T cells (FoxP3 + ) was not statistically different between the groups. These results indicate that MSI CRC is associated with a specific cytokine expression profile that includes CCL5, CXCL10, and CXCL9, which are involved in the T helper type 1 (Th1) response and in the recruitment of memory CD45RO + T cells. Our findings highlight the major role of adaptive immunity in MSI CRC and provide a possible explanation for the more favorable prognosis of this CRC subtype.